Mortuary management and public health - Jaffar Hussain , A P; Khaja Mohiddin, Shaik (Journal of Indian Academy of Forensic Medicine, 2021)
Mortuary is the place where autopsy of human beings where death due to unnatural circumstances is conducted. An attempt has been  made by the investigators to conduct a study related to the standards of present mortuaries and to address the requirement for future  challenges. A total of 16 autopsy centres were selected for the study during the period 2018-2019. This study is based on the  available information provided from different mortuaries. Three teaching hospitals, five area hospitals and eight rural hospitals were  selected. Post-mortem examination in Telangana state are done in designated hospitals run by the Government only. Teaching  hospital mortuaries are provided with relatively good facilities like sanitation, permanent water supply, waste disposal and  incineration plants as compared to area hospitals and rural hospitals. Menace of rodents is seen in all mortuaries present in teaching  hospitals, area hospitals and rural hospitals. Addiction to alcohol is frequently seen among mortuary workers and even among the  doctors. Number of post-mortem examinations in teaching hospitals is higher compared to area and rural hospitals. There are several  areas in mortuaries, which are prone to producing infections and foul smells. As the bodies start decomposing, the foul smell  increases and hence bacteria are also abundant in these areas. Extensive biological waste is produced. Maggots and other insects, all  add to the poor conditions within mortuaries. All together the atmosphere in and around mortuary is poor and renovation of  mortuaries is the need of the day.
Keywords: Mortuary; Autopsies; Public Health; Sanitation; Environment